Persistent Sputum Cellularity and Neutrophils May Predict Bronchiectasis. Issue 4 (2011) - Drost, Nicole; D'silva, Liesel; Rebello, Ryan; Efthimiadis, Ann; Hargreave, Frederick E; Nair, Parameswaran
Abstract : BACKGROUND: Quantitative cell counts in sputum provide an accurate assessment of the type and severity of bronchitis. OBJECTIVE: To examine whether sputum cell counts could identify bronchiectasis in patients with recurrent bronchitis. METHODS: A retrospective survey of a clinical database (January 2004 to January 2005) of quantitative cell counts from sputum selected from expectorate in patients with obstructive airways diseases was used to identify predictors of bronchiectasis using ROC curves. This was prospectively evaluated (February 2005 to April 2008) using high-resolution computed tomography scans of thorax that were independently scored by a radiologist who was blinded to the clinical details. RESULTS: The retrospective survey identified 41 patients with bronchiectasis among 490 patients with airway diseases. Total cell count of 60×10 6 /g or greater of the selected sputum with predominant neutrophils on two occasions had a sensitivity of 86.7%, a specificity of 87.5%, and positive and negative predictive values of 93% and 78%, respectively, to identify bronchiectasis. In the prospective study, 10 of 14 (71%) patients who met these criteria were identified to have bronchiectasis. Both total cell count and the percentage of neutrophils correlated with radiographic bronchiectasis severity. CONCLUSIONS: Persistent or recurrent intense sputum cellularity with neutrophilia is suggestive of bronchiectasis.